ENGAGING MUSIC-PEDAGOGY STUDENTS IN ONLINE COURSE - Bezemchuk, Larysa; Sokolova, Alla; Binytska, Kateryna (The Modern Higher Education Review, 2023)
The article examines the current problems of providing learning online for music teacher students studying at pedagogical universities in the speciality 014 Secondary Education (Musical art). A review of the latest research in the context of the adopted educational standards and the implementation of the ideas of the New Ukrainian School requires the search for effective ways of working with students through digital education. The training of music teacher students based on the principles of integrated learning takes into account the didactic skills associated with the involvement of specialists of musical specialities in artistic and creative activities based on the didactic module (perception-performance, creation and evaluation of the results of artistic activity). The work presents the method of teaching students online based on modular structure. The methodology was implemented in the conditions of online learning on the example of students mastering the integrated course “Methodology of teaching “Art” at school”. Taking into account the specifics of this educational discipline, which reveals modern integrated approaches to teaching art at school, we structured the stages of its study according to the levels of student involvement in working with digital tools (cognitive- developmental, constructive and creative). An attempt was made to offer students at each stage of education the performance of professionally oriented situations. “Lecture-consilium” is defined as an effective form of working with a student audience in synchronous mode, using ICT for the presentation of creative projects in integrated “Art” lessons. A separate place is given to examples of conducting a review and advisory session, in the form of a flex model. The method of teaching students through the means of telecommunication with the use of graphic and symbolic means is presented. It included working with electronic textbooks, using the tools “Саnva”, “LearningApps”, “Сubase 12”. According to the goals of the work, the effectiveness of the methodology of learning online during the assimilation of integrated course using criteria that determine the level of integration and pedagogical skills of future music teachers has been proved. Also, a preliminary analysis of the impact of the online method on motivation of music-pedagogy students and the increase of creative motivation in the performance of art (instrumental, vocal, choral creativity) using innovative learning technologies has been done. Learning outcomes were studied through successful completion of professionally-based tasks, which included designing art lessons, creating art projects, and digital tools. In order to obtain preliminary results and check the effectiveness of the method of teaching online students of pedagogical universities majoring in 014 Secondary Education (Musical Art), the study was conducted in groups of the full-time and part-time students of the H.S. Skovoroda Kharkiv National Pedagogical University in the Department of Musical Art. Three criteria were selected: informational and motivational demonstrated a degree of awareness in the information environment, the ability to perceive artistic information on the Internet, complete professionally-based assignments via online resources. Analytical and active criterion is students’ ability to create art projects and conducting lessons during pedagogical practice online. Active-transformative, which reflected the manifestations of the creative motives of the applicants during artistic and creative activities (perception-performance-creation-evaluation of work) in online education. The results show that online learning method for music-pedagogy students described here is likely to be provided as a basis for modern methods of online learning.